2017
DOI: 10.1016/j.optlastec.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive curvature sensor based on asymmetrical twin core fiber and multimode fiber

Abstract: A highly sensitive curvature sensor based on asymmetrical twin core fiber (TCF) and multimode fiber (MMF) is proposed and experimentally demonstrated. By applying the coupled-mode theory and equivalent refractive index model, we theoretically analyze the uncoupled feature of the TCF and the relationship between peak wavelength and the curvature. Two segments of MMF used as beam splitter and combiner are embedded on the two ends of the TCF, and the extinction ratio of the comb transmission spectrum is about 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Table 1 shows that the sensitivities of the proposed sensor have higher curvature sensitivity and temperature sensitivity than those of the PCF-MZI and FBG (4.06 nm/m −1 and 6.3 pm/ ) ℃ [8], and MMF-PCF-MMF inscribed FBG (−1.36 nm/m −1 and 60.3 pm/℃) [9]. However, the sensor we report has lower curvature sensitivity than the four-core fiber multipath MZI (20.18 nm/m −1 ) [28], MMF-TCF(twin core fiber)-MMF (103.35 nm/m −1 ) [30], and MMF-TCSMF-MMF (−28.29 nm/m −1 ) [31], respectively, because TCSMF, TCF, and four-core fiber are a kind of specialty optical fibers with the multi-core structure separately containing only one core mode. The curvature and temperature resolutions of the sensor can be obtained by using the error analysis method when the resolution ( Dip) δ Δ of the OSA is known, and the curvature and temperature resolutions of the sensor can be represented by [32] Dip2, Dip1, Dip2, Dip1,…”
Section: Resultsmentioning
confidence: 94%
“…Table 1 shows that the sensitivities of the proposed sensor have higher curvature sensitivity and temperature sensitivity than those of the PCF-MZI and FBG (4.06 nm/m −1 and 6.3 pm/ ) ℃ [8], and MMF-PCF-MMF inscribed FBG (−1.36 nm/m −1 and 60.3 pm/℃) [9]. However, the sensor we report has lower curvature sensitivity than the four-core fiber multipath MZI (20.18 nm/m −1 ) [28], MMF-TCF(twin core fiber)-MMF (103.35 nm/m −1 ) [30], and MMF-TCSMF-MMF (−28.29 nm/m −1 ) [31], respectively, because TCSMF, TCF, and four-core fiber are a kind of specialty optical fibers with the multi-core structure separately containing only one core mode. The curvature and temperature resolutions of the sensor can be obtained by using the error analysis method when the resolution ( Dip) δ Δ of the OSA is known, and the curvature and temperature resolutions of the sensor can be represented by [32] Dip2, Dip1, Dip2, Dip1,…”
Section: Resultsmentioning
confidence: 94%
“…Meanwhile, the MZI with different length of PCF also shown high fringe visibility, the max attenuation depth of which were about 17.2 dB, 20.3 dB, 19.9 dB and 24.1 dB, respectively, as illustrated in Figure 3 . The max fringe visibility of our proposed MZI with SMPS fiber structure was higher than those of MZI with TCF-MMF-TCF structure (21 dB) [ 34 ] or MMF-TCSMF-MMF structure (14 dB) [ 35 ], MZI based on asymmetrical twin core fiber and multimode fiber (15 dB) [ 36 ] and some PCF interferometer structures, such as PCF-MZI with two waist-broadened tapers (11 dB) [ 37 ] or with up-tapered joints (11.5 dB) [ 38 ], normal PCF-MZI (21 dB) [ 28 ], TC-PCF MZI (10 dB) [ 16 ], TCF-PCF structure MZI (20 dB) [ 39 ] and S-tapered PCF (12 dB) [ 40 ]. In addition, it can be observed that the insertion loss of the proposed MZI is larger than that of MZI with SMF-PCF-SMF structure [ 8 ], which is due to the increase in the number of fusion.…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…The bent fiber is normally approximated as an arc of the circle when the moving stage moves towards the fixed stage. The curvature of the fiber sensor can be calculated as [ 23 ] where L and d are the initial distance and the movement distance of the moving stage, respectively. Figure 6 a shows the transmission spectra of the sensor under different bending curvatures at room temperature (20 °C).…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%